Productivity of irrigated jambu under soil-water stresses and nitrogen doses - de Aviz, William L.C.; de Lima Junior, Joaquim A.; da Silva, André L.P. [UNESP]; de Oliveira, Pedro D.; Gama, Cândido M.P. (FapUNIFESP (SciELO), 2020)
Jambu (Acmella oleracea (L.) R.K.) is a short-cycle leafy vegetable from the Amazon region, which needs an adequate availability of water and nutrients, mainly nitrogen, to obtain a rapid mass increase. This research aimed to study the effect of different soilwater stresses and nitrogen doses on jambu cultivation in the state of Para. The experiments were conducted at the Igarape-Acu experimental farm of the Federal Rural University of Amazonia (UFRA). The Jamburana variety was used in a 10 × 10 cm spacing, using a randomized block design in a 4 × 4 factorial scheme with three replications. Each plot had a dimension of 0.4 × 0.5 m (0.2 m2), totaling 20 plants in 4 rows, but only the plants of the central rows were useful. Treatments consisted of four soil-water stresses (12, 18, 24, and 30 kPa) as an indication of the irrigation time (critical stress), using drip irrigation, and four nitrogen doses (0, 50, 100, and 150 kg ha-1). The use of soil-water stress of 12 kPa associated with nitrogen fertilization at a dose of 150 kg ha-1 is recommended for better development and production of jambu under the conditions this experiment was conducted.
Keywords: Acmella oleracea (L.); Dripping; Nitrogen fertilization; R.K.; Tensiometry